Pengembangan Platform Tiktok Sebagai Media Pembelajaran Ekstrakurikuler Tata Busana Di SMK Tekstil Pandaan - Berlian Puteri Maharani; Peppy Mayasari; Imami Arum Tri Rahayu; Deny Arifiana (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research applied to 21 of 12th grade Fashion Extracurricular students of Vocational Senior High School Tekstil Pandaan. The purpose was to (1) describe the validation level of Tiktok platform as a learning media; (2) describe the student learning result after the learning media was given; and (3) describe the student response after the learning media was given. Method used in this research was Research and Development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The learning media were validated by media and subject experts using media validation form, applied in class with project assignment given in assignment form, and applied google form to get the student to respond. Data analyzed in a descriptive qualitative way. The result shows that the video tutorial learning media gains the result score of 4,55 of maximum 5, concluded as very valid, the video learning media can help students reach eligibility level of 100% of 75% minimum standard, concluded as eligible, and the results of student responses reached 60% for the strongly agree category and 40% for the agree category regarding the use of Tiktok media as learning media for Fashion Design extracurricular at Pandaan Textile Vocational High School.